Jual Beli Online Melalui Tik Tok Shop Menurut Perspektif Qawaid Fiqhiyah - Azmin, Muhammad; Rahmat, Rahmat; Sasmita, Rindi (Journal of Sharia Economy and Islamic Tourism, 2023)
Abstract: In the digital era, technological developments have brought significant changes in the business world, including increasingly popular online buying and selling methods. One platform that dominates the market share is TikTok Shop, where users can sell and buy products online. This study aims to examine online buying and selling transactions through TikTok Shop from the perspective of Qawaid Fiqhiyah, namely the principles of Islamic law that govern aspects of life, including muamalah or business transactions. This study uses an analytical descriptive approach to analyze the implementation of Qawaid Fiqhiyah in online buying and selling transactions through TikTok Shop. The results of the analysis show that the implementation of Qawaid Fiqhiyah in online buying and selling transactions through TikTok Shop can present challenges and opportunities. Fairness in transactions needs to be maintained so that all parties feel treated fairly. Fulfillment of promises is the main key to building trust between sellers and buyers. In addition, ownership provisions, usury prohibitions, and price provisions also need to be considered so that transactions remain in accordance with Islamic values.Abstrak: Dalam era digital, perkembangan teknologi telah membawa perubahan signifikan dalam dunia bisnis, termasuk metode jual beli online yang semakin populer. Salah satu platform yang mendominasi pangsa pasar adalah TikTok Shop, di mana para pengguna dapat menjual dan membeli produk secara online. Studi ini bertujuan untuk mengkaji transaksi jual beli online melalui TikTok Shop dari perspektif Qawaid Fiqhiyah, yaitu prinsip-prinsip hukum Islam yang mengatur aspek-aspek kehidupan, termasuk muamalah atau transaksi bisnis. Studi ini menggunakan pendekatan deskriptif analitis untuk menganalisis implementasi Qawaid Fiqhiyah dalam transaksi jual beli online melalui TikTok Shop. Hasil analisis menunjukkan bahwa implementasi Qawaid Fiqhiyah dalam transaksi jual beli online melalui TikTok Shop dapat menghadirkan tantangan dan peluang. Keadilan dalam transaksi perlu dijaga agar semua pihak merasa diperlakukan secara adil. Pemenuhan janji menjadi kunci utama untuk membangun kepercayaan antara penjual dan pembeli. Selain itu, ketentuan kepemilikan, larangan riba, dan ketentuan harga juga perlu diperhatikan agar transaksi tetap sesuai dengan nilai-nilai Islam.